To Touch or Not to Touch: Evaluating Student Laboratory Outcomes of Hands-On versus Visual Examination of Prosected Cadavers - Jennifer F. Dennis; Bradley A. Creamer (MDPI AG, 2022)
We utilized the physical manipulation of cadaveric donors by students to evaluate learning outcomes in two undergraduate anatomy courses. Students (n = 176) were assigned as those whom 'manipulated' (n = 100) or 'did not manipulate' (n = 76) donors, and data were compared to performance on laboratory assessments. A Fisher's exact test was conducted within individual and combined course populations to assess if the relationship between physical touch and receiving a passing grade is more than expected by chance. BIO 201 'manipulating' students received a 'C' or better (n = 58) vs. 6 D, F, or Withdraw grades (DFW) on lab practicals as compared to those who did not manipulate (n = 33 DFW vs. 18 C or better) (p < 0.0001). BIO 221 'manipulating' students (n = 34) received a 'C' or better vs. DFW grades (n = 2), while 'non-manipulating' students were able to earn outcomes of 'C' or better (n = 13 vs. 12 DFW). However, students involved in donor manipulation were more likely to receive a 'C or better' (p = 0.0002). Analysis of the data as a single cohort indicates non-manipulating students are 7.24 times more likely to earn a 'DFW' on lab practicals, demonstrating that students are better prepared for laboratory assessments when encouraged to manipulate anatomical structures.